2022
DOI: 10.1007/s43832-022-00015-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of water quality, socio-economic status and policy intervention in spring ecosystems of Tripura, Northeast India

Abstract: Spring is vital in all hilly areas. Without question, springs have aided in the advancement of human civilization. Mountain springs supply water to rural families in the Northeast. This spring ecological study was conducted in Dhalai, Tripura, with socio-economic policy significance. The springs chosen were Jamircherra (JS) and Govindabari (GS). The seasonal features of each spring were studied. The monsoon season is used to bring the life-giving flow of perennial springs. Several water quality indicators like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Dhalai district is ecologically vulnerable, with underdeveloped infrastructure and remoteness. The research area receives an above-average amount of rain each year (2150 mm), 70% of which falls during the monsoon season (April-September) (Barman et al, 2022).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Dhalai district is ecologically vulnerable, with underdeveloped infrastructure and remoteness. The research area receives an above-average amount of rain each year (2150 mm), 70% of which falls during the monsoon season (April-September) (Barman et al, 2022).…”
Section: Study Areamentioning
confidence: 99%
“…Mountain spring water is regarded as the primary source of freshwater that meets the needs of various sectors such as industrial, agriculture, domestic, and other sectors (Agarwal et al, 2013;Das et al, 2018; Barman et al, 2022). Mountain spring water is the most dynamic natural resource because of the important function it plays in the upkeep of the ecological system, as stated by Das (2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a number of research work has been done on water quality in Tripura (e.g. Barman et al 2022 ; Karmakar and Singh 2021 ; Roy et al 2021 ; Roy and Manna 2021 ; Paul et al 2019 ; Singh and Kumar 2015 ; Lodh et al 2014 ; Sarkar and Mishra 2014 ; Banerjee et al 2011 ). Based on the bibliometric analysis, maximum research follows water quality parameters based on micro-spatial scale.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that food-related health problems are directly or indirectly associated with water [21,22]. Failure to ensure drinking water quality may expose food outlet customers and the community to the risk of outbreaks of many infectious diseases [23,24]. As a result, the importance of clean water to human health and well-being is encapsulated in the Human Right to Water and Sanitation, which states that "everyone has the right to obtain clean, sufficient and affordable water for personal and domestic uses" reaffirmed by the United Nations General Assembly and Human Rights Council [25].…”
Section: Introductionmentioning
confidence: 99%